2021
DOI: 10.1177/00031348211038556
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management and Outcomes of Injuries to the Inferior Vena Cava: A Prospective Multicenter Trial From PROspective Observational Vascular Injury Treatment

Abstract: Introduction Injuries to the inferior vena cava (IVC), while uncommon, have a high mortality despite modern advances. The goal of this study is to describe the diagnosis and management in the largest available prospective data set of vascular injuries across anatomic levels of IVC injury. Methods The American Association for the Surgery of Trauma PROspective Observational Vascular Injury Treatment (PROOVIT) registry was queried from November 2013 to January 2019. Demographics, diagnostic modalities, injury pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Other datasets such as the PROspective Observation Vascular Injury and Treatment (PROOVIT) registry may be useful for this type of analysis in the future, or for looking more closely as injury type: such as how do the management strategies or outcomes between transection versus partial transection versus occlusion differ. (42) In addition, there is no information regarding follow-up and long-term outcomes including functional outcomes. Similarly, this may also be useful for comparing how outcomes compares across repair type, such as vein or synthetic graft interposition, or type of endovascular intervention (e.g., stent, embolization, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Other datasets such as the PROspective Observation Vascular Injury and Treatment (PROOVIT) registry may be useful for this type of analysis in the future, or for looking more closely as injury type: such as how do the management strategies or outcomes between transection versus partial transection versus occlusion differ. (42) In addition, there is no information regarding follow-up and long-term outcomes including functional outcomes. Similarly, this may also be useful for comparing how outcomes compares across repair type, such as vein or synthetic graft interposition, or type of endovascular intervention (e.g., stent, embolization, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to outcomes, the PROOVIT database is limited to the acute setting and evaluation of in-hospital complications and mortality. 17,19,26 There is certainly need for additional research into the long-term use of AC and AP for management after repair of a vascular injury, but that is beyond the scope of this analysis. This work may help guide AT therapy choice during the acute peri-trauma period, and future studies may help guide the management in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The American Association for the Surgery of Trauma (AAST) PROOVIT registry is a AAST Multicenter Trial that enrolls patients with injuries to named arterial and venous structures. 13,17,18,19 This database captures patient demographics, admission physiologic data, detailed information on the type and management of vascular injuries, and any data on imaging from the vascular laboratory. Patients are included if >2 years old with imaging, clinical, and/or operative evidence of injury to a named vessel.…”
Section: Characteristics Of Cohortmentioning
confidence: 99%
“…While specificity and predictive value are high in this patient population and geography, performance of this study at a single level 1 urban center study with a high percentage of penetrating trauma that may make these results less generalizable to other centers, though this limitation may be improved with the inclusion of more patients and broadening the model to include institutional factors. [45][46][47][48][49][50] Our choice to use final-coded AIS scores as present (by design) in the trauma registry database as proxy indicators for admission diagnostic data introduces a degree of retrospective bias into the network, potentially exaggerating the precision of the predictive values reported. We felt this was the most appropriate and expedient source of data for this proof of concept study in this population, however, as our selection criteria for patients with an at least two-midnight stay limits the study to a subpopulation in which confirmed diagnostic changes to the admission information (e.g.…”
Section: Discussionmentioning
confidence: 99%